ANALISYS OF FRACTIONAL-N FREQUENCY SYNTHESIZERS - B. I. Shakhtarin; E. G. Kacharmina; V. V. Veltishev (Научный вестник МГТУ ГА, 2018)
Modern information and control systems cannot be imagined without synchronization subsystems. These are the basic elements that provide tracking of the frequency and phase of reference and information signals, the evaluation of information parameters, and the synthesis of reference and clock signals. Frequency synthesizers (FS) are widely used due to the high speed of frequency setting, a wide range of frequency grids and minimal phase noise in the operating frequency range. Since with the mass appearance of specialized microprocessors and with the improvement of automatic design systems, the feasibility and repeatability of products has become simpler, digital FS are increasingly being used. The most widely used are FS with a frequency divider on digital elements, which serves to convert the signal of a reference oscillator and a controlled generator. For FS using a divisor with an integer division factor in the feedback loop, there are a number of limitations, such as the lower frequency of the FS and the frequency step of the FS. To solve this problem, divisors with fractional-variable division factors in the feedback loop are used, which allow to obtain the required range and the grid frequency step of the FS. The methods of improving the quality of spectral and dynamic characteristics of digital synthesizers in a given band of frequency detuning are analyzed. The principles of the FS operation with a divisor with a fractionalvariable fission coefficient are described, and structural schemes are given. The results of imitation simulation in the Simulink system of the software package MATLAB of frequency synthesizers with a divisor with a fractional-variable fission factor implemented in various ways are presented, and a comparative analysis of the spectral characteristics of the obtained models is carried out.